Unbalanced N:P ratios and nutrient stress controlling growth and toxin production of the harmful dinoflagellate Prorocentrum lima (Ehrenberg) Dodge - Varkitzi, Ioanna; Pagou, Kalliopi; Granéli, Edna; Hatzianestis, Ioannis; Pyrgaki, Christina; Pavlidou, Alexandra; Montesanto, Barbara; Economou-Amilli, Athena (Harmful algae, 2010)
The responses of the benthic marine dinoflagellate Prorocentrum lima to nutrient stress induced by unbalanced N:P ratios were the subject of this study. Batch cultures of P. lima cells were grown under NP sufficient (N as nitrate and ammonium) and deficient conditions, and the cell growth and toxicity were followed for eight weeks. P. lima grew slowly in all nutrient conditions and net growth rates ranged from 0.11 to 0.22 divisions day −1. Phosphorus (P) was taken up with high uptake rates in all treatments until the end of exponential phase and reached limitation in the P deficient cultures. Nitrogen (N) did not reach limitation in any treatment. In the cultures with nitrate as exclusive N source, uptake rates of nitrate remained high after the exponential phase, suggesting that P. lima cells continued to accumulate N under surplus N availability. Nitrate was slowly consumed and therefore maintained cell growth, as documented by a prolonged exponential phase and an algal biomass increasing at low rates still after seven weeks of incubation. In the cultures with ammonium as exclusive N source, ammonium was taken up with the highest N uptake rates until the end of exponential phase. However, high initial concentrations of ammonium proved to be toxic to P. lima cells, demonstrating growth inhibition with the lowest algal biomass and okadaic acid (OA) production among treatments. The OA production increased after the exponential phase in all nutrient conditions when cell growth slowed down, suggesting that OA production was regulated by growth limitation. The highest OA cellular content (11.27 ± 3.30 pg OA cell −1) was found in the P deficient cultures, where P decreased to limitation after the exponential phase (P < 0.1 μM). We argue that the severely low P concentrations slowed down the growth rate so as to allow for a higher accumulation of OA in the P. lima cells that continued to produce OA at the same rate.